I'm trying this PDE: $$u_t = u_{xx} + g(x);\quad x\in[0,\pi]$$ With boundary conditions: $$u_x (0,t)=u_x(\pi,t)=0$$ And initial condition: $$u(x,0)=f(x)$$ I think variable separation proposing a u(x,t)= X(x)T(t) could be a good approach but: $$Let\quad u(x,t)=X(x)T(t)$$ $$\Rightarrow X(x)T'(t)=X''(x)T(t)+g(x)$$ Then trying to separate I get: $$\frac {T'(t)}{T(t)}=\frac {X''(x)}{X(x)}+ \frac {g(x)}{X(x)T(t)}$$ I don't know how to make that last last function just dependant of one variable. Any ideas or am I taking the wrong path?


If $u$ is a solution of the given problem, then $$ v(x,t)=u(x,t)+\int_{0}^{x}\int_{0}^{x'}g(x'')dx''dx'-\frac{1}{\pi}\int_{0}^{\pi}g(y)dy\, (t+x^{2}/2). $$ is a solution of \begin{align} v_{t} &= u_{t}-\frac{1}{\pi}\int_{0}^{\pi}g(y)dy=u_{xx}+g-\frac{1}{\pi}\int_{0}^{\pi}g(y)dy=v_{xx} \\ v_{x}(0,t) &= u_{x}(0,t) = 0, \\ v_{x}(\pi,t) &= u_{x}(\pi,t)+\int_{0}^{\pi}g(x'')dx''-\frac{\pi}{\pi}\int_{0}^{\pi}g(y)dy = u_{x}(\pi,t)=0. \\ v(x,0) &= u(x,0)+\int_{0}^{x}\int_{0}^{x'}g(x'')dx''dx'-\frac{x^{2}}{2\pi}\int_{0}^{\pi}g(y)dy \end{align} So the inhomogeneous problem is reduced to the equivalent homogeneous problem \begin{align} v_{t} &= v_{xx}, \\ v_{x}(0,t) &= 0,\hspace{5mm} v_{x}(\pi,t) = 0,\\ v(x,0) &= f(x)+\int_{0}^{x}\int_{0}^{x'}g(x'')dx''dx'-\frac{x^{2}}{2\pi}\int_{0}^{\pi}g(y)dy. \end{align}


The short answer is you cannot assume, in general, separation of variables in a non-homogenous problem. Since your boundary conditions are homogenous, solve the alternative problem $\theta_t = \theta_{xx}$ with the same boundary conditions (no matter the initial condition) and then expand:

$$ u(x,t) = \sum_n T_n(t) X_n(x), $$ where $X_n(x)$ are the eigenfunctions of the homogenous problem (I think they are $X_n(x) = \cos{n x}$). Since the functions $X_n$ form a complete basis on $0 \leq x \leq \pi$, any smooth function can be approximated/represented according to the series above.

Plug the series in the original PDE and use the orthogonality properties of $X_n$ to find the coefficients $T_n(t)$, which will satisfy a first order differential equation. The initial condition for $T$ can be extracted from the initial condition of $u$ using, again, orthogonality.

I think this is often referred to as Fredholm's alternative.

Hope this helps!

  • $\begingroup$ Could the downvoter please tell me where I am wrong? $\endgroup$ – Dmoreno May 29 '15 at 3:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.